Characterization of Egg Shell Waste As Adsorbent for Cooking Oil Waste Purification - Gita Indah Budiarti; Alia Ariesanti; Endah Utami; Okka Adiyanto; Utaminingsih Linarti (Universitas Ahmad Dahlan, 2021)
Eggshell has a shaft and a high surface area, so it has the potential to become an adsorbent. The adsorbent is an adsorbent in the filtration process. Waste cooking oil can be reused as raw material with economic value. So far, the waste bank that accommodates used waste has not gone through the filtration process, so the selling price is low. Waste cooking can be filtered using various adsorbent media, including activated carbon, commercial silica, and local adsorbents such as eggshells. A filtration process on waste cooking oil is expected to increase income for waste banks. The objective of this study was to investigate formulations adsorbent from eggshells for purification waste cooking oil. The variables used were a variety of particle size adsorbents (60, 80 mesh) and adsorbent weight (10, 15 g). The optimal result for the decreased acidic number was obtained at 60 mesh particle size, weight 15 grams.